Kontribusi surface area, specific gravity, dan volume telur terhadap berat telur puyuh - Dicky Wahyu; Johar Arifin; Dani Garnida (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
The purpose of this study was to determine the correlation and obtain the amount of contribution between surface area (X1), specific gravity (X2), and volume (X3) to the weight of quail eggs (Y). This study used 300 samples of fresh eggs with the correlation method of the path analysis test. The calculation of the correlation coefficient is pX1Y = 0.924, pX2Y = 0.056, and pX3Y= 0.499. The calculation of the trajectory coefficient is pYX1 = 0.875, pYX2 = 0.235, and pYX3 = 0.888. Based on the results of data analysis in this study, it can be concluded that the surface area is very strongly correlated, the specific gravity is very low, and the volume of eggs is moderately correlated with a correlation of 0.924, 0.056, and 0.499 (P>0.05). The total influence was 86.36% and the influence of other factors was 13.64% with volume being the largest contributing independent variable, which was 42.08%, while surface area was 41.55% and specific gravity being the smallest contributing independent variable at 2.73%.